Hydroxyproline increases inflammation and Uropathogenic E. coli (UPEC) infection in female rats - Parveen Kumar; Zhengqin Yang; Huma Fatima; Tanecia Mitchell (Scientific Reports, 2024)
Abstract Calcium oxalate (CaOx) kidney stones may be associated with urinary tract infections (UTIs). However, the mechanisms for this association are not well-established. The objective of this study was to investigate the effect of oxalate on immunity and UTI development in vivo. Female Sprague-Dawley rats were fed a control diet for 3 days before continuing this diet or starting a 5% Hydroxy-L-proline diet (HLP; oxalate precursor) for 7 days. Rats were subsequently infected transurethrally with Uropathogenic E. coli (UPEC, a bacterium that causes UTI) and sacrificed 3 days later. Urine, blood, kidney, and bladder samples were collected. Urinary oxalate levels, renal CaOx crystal deposition, inflammatory markers, and the bacterial load were assessed using ion chromatography-mass spectrometry, immunohistochemistry, qRT-PCR, western blotting, enzyme-linked immunosorbent assays, or colony forming unit assays. Animals fed HLP and infected with UPEC had a significant increase in urinary oxalate levels, renal CaOx deposition, pro-inflammatory macrophages, pro-inflammatory cytokines, and bacterial loads compared to animals fed the control diet with UPEC infection. In addition, HLP-fed animals had significantly reduced anti-inflammatory renal macrophages and anti-inflammatory cytokine levels in their plasma, urine, and kidneys. These findings suggest that oxalate may play a novel role in the propagation of UTI development.